THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION ON STUDENTS' ENTREPRENEURIAL INTERESTS STATE VOCATIONAL SCHOOL 3 BENGKALIS - Arvika Sari, Rini; Arimurti, Rizqa (JURNAL EKBIS, 2024)
This study examines the impact of entrepreneurship education on students' entrepreneurial interest at SMKN 3 Bengkalis. High unemployment rates in Indonesia are partly due to a lack of job opportunities for high school graduates and a low entrepreneurial spirit. Entrepreneurship education is crucial in shaping students' creativity, independence, and willingness to take risks in starting a business. Using a quantitative descriptive method, the study involved 100 students selected through random sampling. Data were collected via questionnaires and analyzed using the product moment correlation. The findings reveal a significant correlation (r=0.613) between entrepreneurship education and students' entrepreneurial interest, suggesting that exposure to entrepreneurship education increases students' motivation and interest in entrepreneurship. The study recommends enhancing entrepreneurship programs in schools to better prepare students for the business world, fostering an entrepreneurial mindset that contributes to economic development.